Digital preservation ICSTI/CODATA/ICSU Seminar on Preserving the Record of Science, 14-15 February 2002, UNESCO, Paris, France - ICSTI/CODATA/ICSU Seminar on Preserving the Record of Science; Mahon, Barry; Siegel, Elliot R.; International Council of Scientific and Technical Information; International Council for Science; CODATA; International Council of Scientific Unions; Unesco (IOS Press ; Ohmsha, 2002)
Preservation or ""permanent availability"" of the record of science as represented by scientific information is one of the processes which is dramatically affected by the change to an all digital world. This work covers the viewpoints of technologies which are important in the preservation process.
Keywords: Science : Information services : Congresses; Digital preservation : Congresses; Technology : Data processing : Congresses